2023
DOI: 10.30910/turkjans.1208010
|View full text |Cite
|
Sign up to set email alerts
|

Şanlıurfa'da Tescilli Bazı Nohut (Cicer arietinum L.) Çeşitlerinin Verim, Morfolojik ve Kalite Özelliklerinin Değerlendirilmesi

Abstract: Urfa ekolojik koşullarında bazı nohut hat ve çeşitlerinin tarımsal özelliklerinin belirlenmesi amacıyla 2014-2015 yıllarında yürütülen bu çalışma GAP Tarımsal Araştırma Enstitüsüne ait deneme arazilerinde yürütülmüştür. 20 tescilli nohut genotipi ve 3 kontrol çeşidi kullanılarak yürütülen çalışma tesadüf blokları deneme desenine göre üç tekrarlamalı olarak kurulmuştur. Araştırmada nohut bitkisinde %50 çıkış sağlandıktan sonra çiçeklenmeye kadar geçen gün sayısı, bakla bağlama, çıkış sağlandıktan sonra kadar g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…In the study, registered chickpea cultivars, widely cultivated in Central Anatolia, Southeastern Anatolia, Mediterranean, Black Sea, and the Aegean Regions and developed by institutions, were used as plant material. Tolerant Azkan (Aydın et al, 2016) and susceptible İzmir-92 (Mart et al, 2016) cultivars were used as control, total of 15 chickpea cultivars (Hisar, Işık-05, Yaşa-05, Çakır, Çağatay, Arda, Azkan, İzmir-92, Sarı-98, Akçin-91, Uzunlu-92, Gökçe, Aksu, İnci and Hasanbey) were tested.…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study, registered chickpea cultivars, widely cultivated in Central Anatolia, Southeastern Anatolia, Mediterranean, Black Sea, and the Aegean Regions and developed by institutions, were used as plant material. Tolerant Azkan (Aydın et al, 2016) and susceptible İzmir-92 (Mart et al, 2016) cultivars were used as control, total of 15 chickpea cultivars (Hisar, Işık-05, Yaşa-05, Çakır, Çağatay, Arda, Azkan, İzmir-92, Sarı-98, Akçin-91, Uzunlu-92, Gökçe, Aksu, İnci and Hasanbey) were tested.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Overall, the data of several studies conducted in Turkey reveal the unstable nature of the aggressiveness of A. rabiei population in Turkey, which, in turn, explains a frequent resistance overcome in registered chickpea cultivars leading to epidemics (Nalçacı et al, 2021). In the studies carried out in Turkey in recent years, it is reported that four pathotypes of A. rabiei exist (Mart et al, 2016). A diversity of aggressiveness patterns and rapid evolution of highly virulent isolates within the A. rabiei population in Turkey disclose the adaptation plasticity of this destructive and prolific fungal pathogen (Nalçacı et al, 2021).…”
Section: Introductionmentioning
confidence: 99%